Role Identity, Loneliness, and Bereavement During the Pandemic in Japan: A Cross‐Sectional Study - Aya Toyoshima (Health Science Reports)
ABSTRACT Background and Aims The COVID‐19 pandemic significantly restricted social activities, prompting a re‐examination of community dynamics. In Japan, where families are central, the absence of a spouse increases susceptibility to loneliness and isolation. The loss of a spouse, especially during the pandemic, has heightened these issues among middle‐aged and older individuals. Limited quantitative studies on pandemic‐related bereavement in Japan underscore the need to understand the associated risks of loneliness and social isolation. This study aimed to examine the relationships between role identity as a member of the local community, loneliness, and social support among middle‐aged and older adults. This study also examined whether there were differences in the relationships between those who had experienced bereavement and those who had not. Methods An Internet survey was conducted with Japanese adults (aged 50–74 years), including those who experienced bereavement during the pandemic. The final sample included 322 participants (154 in the bereavement group and 168 in the cohabiting group). The variables, measured using psychological scales, included role identity as a local resident, social capital (trust, reciprocity, and membership), loneliness, and social support (family and friendship). Results The higher trust and role identity were related to lower loneliness. Membership in the cohabiting group was related to lower level of loneliness and higher level of social supports. However, membership in the bereavement group was not related to either. Furthermore, trust and reciprocity were related to loneliness and social support. Conclusion These results indicated that the role identity and perception of social capital related to preventing isolation and loneliness for bereaved people.